1983
DOI: 10.1111/j.1746-1561.1983.tb01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Tenets of Inoculation Theory to Develop and Evaluate a Preventive Alcohol Education Intervention

Abstract: With the advent of the Surgeon General's Report, Healthy People, a renewed interest in and concern for the health-risky practices of the school aged has emerged. Moreover, because the mortality rates for the 15 to 24 year age group continues to increase while the mortality rates for every other age group continues to decline, a school health education imperative has become prevention-based interventions. The experimental, prevention-based alcohol education program reported here describes one such intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Inoculation messages are also useful in behavior-change interventions, with participants responding positively (compared to a control group) to inoculations against arguments justifying alcohol consumption [45], the threat of peer-pressure leading to smoking initiation [46], and pro-sugar arguments from soda companies [47]. Inoculation can reduce the influence of conspiracy theories by increasing the degree of scepticism towards conspiratorial claims [48], and has been shown to convey resistance to misinformation regarding agricultural biotechnology [49].…”
Section: Prebunking and Inoculation Theorymentioning
confidence: 99%
“…Inoculation messages are also useful in behavior-change interventions, with participants responding positively (compared to a control group) to inoculations against arguments justifying alcohol consumption [45], the threat of peer-pressure leading to smoking initiation [46], and pro-sugar arguments from soda companies [47]. Inoculation can reduce the influence of conspiracy theories by increasing the degree of scepticism towards conspiratorial claims [48], and has been shown to convey resistance to misinformation regarding agricultural biotechnology [49].…”
Section: Prebunking and Inoculation Theorymentioning
confidence: 99%
“…There were main effects on self –reported behavioural outcomes clearly attributable to research assessments in two other studies [25], [29]. There were also main effects of research assessments on non-behavioural self-reported outcomes in both of these studies and in two additional studies, on knowledge [26] and intentions [23], with an interaction effect also in the latter case.…”
Section: Discussionmentioning
confidence: 66%
“…Inspection of the data in the study by Duryea [26] suggests it is unlikely that there were any interactions between assessment and intervention for either outcome even were this small study to have been very much larger.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…More specifically within health education, affective and social skills such as valuing (Eddy et al 1985), communicating, coping, relaxing (Richardson et al 1983, asserting (Galassi et al 1981), and resisting pressure (Duryea 1983) are also actively explored and promoted using some of the more informal teaching strategies such as sociodrama and role playing (Sleet and Stadsklev 1977). Another contemporary curriculum issue is that of specific-behaviour versus whole person approaches to health education.…”
Section: Health Education Curriculamentioning
confidence: 97%